Rekonstruksi Konsep Riba dalam Tafsir Kontekstual: Analisis terhadap Praktik Pembiayaan PNM Mekaar - Opi Salamah; Hery Sahputra (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study examines the impact of usury on PNM Mekaar's microfinance practices in Belawan through the interpretation of Surah Al-Baqarah 275–279. PNM Mekaar is a financing program for underprivileged women operating ultra-micro businesses, with a joint liability group mechanism, fixed margins or administration fees, and flexible tenors. This study used a qualitative literature review method, with data sources including literature, Quranic exegesis, journals, and official PNM reports. The results indicate that usury can have economic impacts in the form of additional burdens for customers, reduced business sustainability, and increased risk of default. Social impacts include decreased trust in institutions and potential moral conflicts, while spiritual impacts are related to violations of sharia law and the loss of the blessings of profits. The analysis of the interpretation of Surah Al-Baqarah 275–279 reaffirms the strict prohibition of usury and emphasizes fairness and transparency in transactions. PNM Mekaar, which implements interest-free principles through qard al-hasan and murabahah bil wakalah contracts, as well as alternative options such as mudharabah and musyarakah contracts, complies with Sharia principles and supports the sustainability of micro-enterprises. This implementation of Sharia financing not only avoids usury (riba) but also strengthens the economic, social, and spiritual stability of the community.